ANALISA METODE TEOREMA BAYES DALAM MENDIAGNOSA KEGUGURAN PADA IBU HAMIL BERDASARKAN JENIS MAKANAN - Fricles Ariwisanto Sianturi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2019)
An expert system for diagnosing the cause of miscarriage in pregnant women is an expert system designed as a tool to diagnose the type of food that causes miscarriage. Computer programs intended as providers of assistive devices in solving problems in certain areas of specialization such as miscarriage problems in pregnant women. This knowledge is obtained from various sources including books and the internet that are related to the causes of miscarriages. Knowledge base arranged in such a way into a database with several tables of food types and effect tables to facilitate system performance in drawing conclusions in this expert system using the Bayes theorem. This expert system will display the choice of symptoms that can be chosen by the user, where each choice of effects will read the user to the next selection of effects until they get the final result. At the end of the expert system will display the choice of user effects, types of food causes of miscarriages, and solutions.